Investigation of Fatigue Life for Asphalt Concrete Modified by Polymer Additives of Various Types - V. A. Veranko; A. V. Ladyshau; R. K. Hatalski (Наука и техника, 2018)
The paper has analyzed influence of additives representing a group of thermoplastic elastomers and complex thermoplast-based modifiers on fatigue life of asphalt concrete. Regularities in time have been determined in the paper and close values of their physical and mechanical properties have been obtained while using various types of binders and modifiers. Statistic and laboratory investigations have made it possible to obtain theoretical parameters of the fatigue life for materials used for road dressing. The analysis has been based on statistical values of ordinary and modified asphalt concrete and asphalt concrete mixes of C- and A-type obtained during the experiments for the period from 2010 till 2016. A statistic analysis has permitted to compare a parameter Ипл (resistance index to plastic deformations) with such parameters as ny (number of elastic constraints) and Rc (threshold structural strength). 12 calculations (Nos. 1–12) have been carried out in order to realize targets of the second investigation. Calculative characteristics of asphalt concrete required for determination of reliability parameters have been estimated in the paper. A bottom layer of twoor three-coat pavement has been selected as an object of the investigation due to the fact that it is more often subjected to an impact of cyclic tensile stresses caused by a transport load. The required value for calculation of tensile stresses s at calculated temperature 0 has been accepted on the basis of executed estimations while using finite elements method and distribution of stresses has been determined along structure with 20 cm thickness due to load А2. Corresponding conclusions have been made in accordance with the obtained results.